HUBUNGAN FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEPATUHAN IBU TERHADAP PEMBERIAN IMUNISASI DASAR PADABAYI DI PUSKESMAS ANDALAS - Safara Innas; Melya Susanti; Mashdarul Ma’arif (Yayasan Nusantara Hasana Berdikari, 2025)
Immunization is one of the most effective and efficient public health strategies for preventing various diseases, such as polio, smallpox, tuberculosis, hepatitis B, diphtheria, measles, rubella, CRS, tetanus,pneumonia, and meningitis. However, maternal compliance with immunization is often influenced by several factors, such as lack of knowledge, awareness, timing of immunization, immunization side effects, maternal education, beliefs, and attitudes. This research to determine correlation of factors affecting level of maternal compliance with providing primary immunization of infants at Andalas Health Center. This research is based on pediatric and immunology. The research was conducted in April – December 2024. It uses an unpaired categorical analytic design with 74 respondents selected through consecutive sampling. The data were analyzed univariately in the form of frequency distributions and bivariately using the chi-square test. The characteristics of mothers based on age were mostly 20-35 years as much as 49 person (66,2%), high school education as much as 45 person (60.8%) and employment status is not working as much as 54 person (73.0%). The highest level of compliance was obedient as much as 59 person (79.7%), good knowledge as much as 56 person (75.7%), self efficacy was sure as much as 61 person (82.4%), easy access to services as much as 64 person (86.5%), supportive family support as much as 45 person (60.8%) and supportive health workers as much as 58 person (78,4%). There is a significant correlation between knowledge, education, self efficacy, access to services, family support, health worker support on the level of maternal compliance with primary immunization at the Andalas Health Center with a p-value <0.05. While there is no significant correlation between employment status with p-value 0.493 (>0.05). There is a correlation between knowledge, education, self-efficacy, access to services, family support, health worker support on the level of maternal compliance with primary immunization.